Property market nature and the choice of property portfolio diversification strategies: The Nigeria experience - Olaleye, Abel (International Journal of Strategic Property Management, 2010)
With a focus on the Nigerian property market, this paper considered and empirically analyzed how property market nature and the perception of market players of some qualitative factors have impacted on choice of property portfolio diversification strategies. Questionnaires, backed up with interviews, were administered on 28 institutional property investors and 159 real estate practitioners in three commercial nerve centres of Nigeria, namely, Lagos, Abuja and Port‐Harcourt metropolitan areas. The frequency distribution analyses’ results revealed that the Nigerian property market was an emerging one and, as it is expected, there was dearth of time series data while investors in the market were small time institutional investors. Using mean rating on a 4‐point rating scale, the study found six factors, arising from the nature of the property market, as the significant factors impacting on choice of diversification strategies. These are: the investors’ overall expectation of the benefits of diversification scheme, the need to reduce management operating costs, management convenience, operating environment, market players’ education and knowledge of alternative diversification techniques and availability or otherwise of data in the market. The result of cross tabulation and Chi‐square test also indicated that there was a statistically significant relationship between educational qualifications of practitioners and their choice of diversification strategies.First published online: 18 Oct 2010